In-Situ Study On Improvement Of Soft Ground Using Stone Columns For Railway Embankment - Kishore Kumar B.; Srini Naik B.; Eswaran Prasad C R; Ramakrishna Raju N (Deep Foundations Institute, 2022)
The authors through this paper intend to introduce the non-vibro technique of ground improvement by stone column, being used for the first time in India under the Western Dedicated freight Corridor in Mumbai area. New 2x25 KV double line dedicated freight corridor tracks, capable of carrying 32.5-ton axle load are proposed to be built on this stretch. Non-Vibro Displacement Stone Columns of 900 mm diameter were installed to improve the safe bearing capacity of the soft ground to take the loading of Dedicated Freight Corridor Railway embankment. Vertical footing load tests on single and three column groups were conducted to assess the improvement in the sub-surface condition after installation of stone columns. This paper describes load tests conducted on stone columns and analysis of the obtained results. The observed load settlement behaviour of the improved ground has also been presented. Behaviour of single and group of stone columns have been compared and criteria adopted for arriving at desired factor of safety based on the settlement observed, has also been discussed.